Same Same, but Different? Relations between Facets of Conscientiousness and Grit. Issue 6 (November 2018) - Schmidt, Fabian T.C.; Nagy, Gabriel; Fleckenstein, Johanna; Möller, Jens; Retelsdorf, Jan
The constructs grit and conscientiousness are closely connected. However, this relationship has not been analysed while accounting for the complex structure of conscientiousness and the multifaceted conception of grit (perseverance of effort; consistency of interest). In this study, we analysed the connection while considering the hierarchical structure of conscientiousness, differentiating between a superordinate factor, a first–level common factor (industriousness), and lower level unique factors. Drawing on two samples ( N = 413, M age = 15.29, and N = 530, M age = 31.75), we applied an extension procedure for confirmatory factor analysis that enables a simultaneous investigation of the relationships on all levels. The perseverance facet of grit was tightly aligned to the common factors (95% shared variance) and was strongly related to the industriousness factor. Consistency shared less variance with the common factors of conscientiousness (53%), but it was additionally correlated with the self–discipline facet. The results for the global grit scale were most similar to the results for perseverance. Grit appears to be a construct that combines the superordinate and industrious aspects of conscientiousness and shares the unique aspect of the self–discipline facet; this suggests that grit and its facets can be fully integrated into the hierarchical structure of conscientiousness.